Generalized minimum variance control under long-range prediction horizon setups. (May 2016) - Silveira, Antonio; Trentini, Rodrigo; Coelho, Antonio; Kutzner, Rüdiger; Hofmann, Lutz
Abstract: This paper presents the design and evaluation of a minimal order Generalized Minimum Variance controller with long-range prediction horizon and how it affects the controller and plant output variances. This study investigates how the increased prediction horizon can contribute to mitigate stochastic disturbances and attenuate oscillations. In order to design high order prediction minimum variance filters, a design procedure independent of the Diophantine Equation solution is used. The evaluation is conducted through simulations and practical essays with two different plants: a first order water flow rate problem and a second order under-damped electronic circuit. Both problems are assessed under an incremental control scheme and based on identified stochastic models. Also, two optimal tuning procedures for the algorithm are proposed. Abstract : Highlights: Evaluation of how long-range prediction horizons affects minimal order GMV controllers. Evaluation of extended prediction horizons aiming stability improvement. Experimental tests with long-range, high-order predictors.